ROLE ARTIFICIAL INTELLIGENCE IN REDUCING PRODUCT COSTS AGRICULTURAL "APPLIED STUDY IN THE NATIONAL PROGRAM FOR THE DEVELOPMENT OF WHEAT CULTIVATION IN IRAQ - Dr. Mohammed Abdelwahid Flayyih; Hadeel Ahmed Badr; Shaymaa Majeed Saeed (American Journals, 2022)
The aim of the research is to identify contemporary technologies and their use in the agricultural sector, as it is a vital and important sector. As artificial intelligence techniques have been used to reduce the costs of the agricultural product represented by the cost of direct wages, as the reliance on traditional methods of cultivation and production leads to higher costs and crop production of low quality . The researchers relied on the inductive and deductive approach to enhance the theoretical aspect, while the practical aspect The researchers relied on analyzing the data obtained from the National Program for the Development of Wheat Cultivation in Iraq, and the researchers concluded that artificial intelligence has a major role in reducing the costs of the agricultural product represented by the costs of direct wages, which is reflected in the result in reducing costs.
Keywords: artificial intelligence, reducing agricultural product costs.